Promotion of Cervical Cancer Cell Proliferation by miR-130b Expression Level Changes and Inhibition of its Apoptosis by Targeting CDKN1A Gene - Wang, Yanli; Yang, Lei; Fan, Caihong; Mu, Hong; Han, Munan; Liu, Tao; Xie, Lili; Gao, Qiang (Current Cancer Drug Targets, 2022)
Background: Dysregulation of miR-130b expression is associated with the development of different cancers. However, the description of the biological roles of miR-130b in the growth and survival of cervical cancer cells is limited. Methods: The miR-130b levels in cervical cancer cells during different stages of growth were determined using reverse transcription-quantitative PCR. The methylation level of DNA sequences upstream of the miR-130b gene was measured using an SYBR Green-based quantitative methylation- specific PCR. Reverse transcription-quantitative PCR, Western blotting, and fluorescence report assays were used to identify the miR-130b-targeted gene. Cell counting kit-8 and comet assays were used to determine cell viability and DNA damage levels in cells, respectively. EdU Apopllo488 in vitro Flow Cytometry kit, propidium iodide staining, anti-γ-H2AX antibody staining, and Annexin-V apoptosis kit were subsequently used to determine DNA synthesis rates, cell cycle distribution, count of DNA double-strand breaks, and levels of apoptotic cells. Results: miR-130b levels increased at exponential phases of the growth of cervical cancer cells but reduced at stationary phases. The methylation of a prominent CpG island near the transcript start site suppressed the miR-130b gene expression. MiR-130b increased cell viability, promoted both DNA synthesis and G1 to S phase transition of the cells at exponential phases, but reduced cell viability accompanied by accumulations of DNA breaks and augmentations in apoptosis rates of the cells in stationary phases by targeting cyclin-dependent kinase inhibitor 1A mRNA. Conclusion: miR-130b promoted the growth of cervical cancer cells during the exponential phase, whereas it impaired the survival of cells during stationary phases.
Keywords: growth